Stable isotopes in arid and semi-arid forest systems - Ferrio, J.P.=700 1 Resco, V.; Williams, D.G.; Serrano, L.; Voltas, J.
(Es, En)
ilus., 58 ref.
Keywords: ECOLOGIA FORESTAL; FISIOLOGIA VEGETAL; ISOTOPOS; SEQUIA; USO DEL AGUA; CLIMA; ESPAÑA